(untitled) (Pulse, 2026)
The purpose of this article is to report an incidental finding of a clinically significant anti-A1 antibody while detecting blood group of an elderly patient. As this antibody is reactive at 37oC, this may cause destruction of transfused A1 red cells and this is the cause of clinical significance. Usually anti-A1 antibodies in plasma are naturally occurring antibodies, not clinically significant because they react best below room temperature, not at body temperature sometimes causing discrepancy during routine blood grouping and crossmatching. For this particular case, some precautions should be taken before blood transfusion to avoid hemolysis. Pulse Volume 17, Issue 2 2025; 38-40